2022
DOI: 10.1371/journal.pone.0278711
|View full text |Cite
|
Sign up to set email alerts
|

Ribitol alters multiple metabolic pathways of central carbon metabolism with enhanced glycolysis: A metabolomics and transcriptomics profiling of breast cancer

Abstract: Breast cancer is heterogenous in development and cell population with prognoses being highly dependent on numerous factors from driving mutations, biomarker expression and variation in extracellular environment, all affecting response to therapies. Recently, much attention has been given to the role of metabolic alteration in cancers, expanding from the Warburg effect to highlight unique patterns in different cancer cell populations for improving diagnostic and therapeutic approaches. We recently reported on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
2
1
Order By: Relevance
“…This result contrasts with early reports that enhanced matriglycan expression is associated with inhibition of cancer growth and invasion [5][6][7]. Our follow-up study to understand the metabolic effect of ribitol by metabolomics revealed that ribitol-induced enhancement in matriglycan is associated with an alteration in glycolysis in MCF-7 cells [8]. Considering that breast cancers are heterogeneous in cell types with variation in metabolic pathways, the effect of ribitol treatment on cell growth may vary cell-type dependently.…”
Section: Introductioncontrasting
confidence: 96%
“…This result contrasts with early reports that enhanced matriglycan expression is associated with inhibition of cancer growth and invasion [5][6][7]. Our follow-up study to understand the metabolic effect of ribitol by metabolomics revealed that ribitol-induced enhancement in matriglycan is associated with an alteration in glycolysis in MCF-7 cells [8]. Considering that breast cancers are heterogeneous in cell types with variation in metabolic pathways, the effect of ribitol treatment on cell growth may vary cell-type dependently.…”
Section: Introductioncontrasting
confidence: 96%
“…Increasing interest in the relationship between systemic metabolism, tumor metabolism, immunometabolism, and cancer outcomes, alongside evolving technologies expanding both the available data and the community's ability to mine it to develop new insights. To that end, in this study, we utilized multiple publicly available breast cancer datasets, including "ACRIN-FLT-Breast (ACRIN 6688)", TCGA BRCA "Phenotypes", TCGA BRCA "IlluminaHiSeq", "TCGA TARGET GTEx", "Node-negative breast cancer (Desmedt 2007)", "ICGC (donor centric)", As opposed to genes or metabolic fluxes involved in glucose [24][25][26][27][28][29][30][31]or lipid metabolism [31][32][33][34][35][36][37][38][39], there exists a relative paucity of studies exploring the impact of expression of genes regulating amino acid uptake in breast cancer. Therefore, we elected to focus the current study on the expression of LAT1, which transports large amino acids including leucine, isoleucine, valine, phenylalanine, methionine, tyrosine, histidine, and tryptophan into the cell, and its relationships with body weight, tumor cell proliferation, and immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…As opposed to genes or metabolic fluxes involved in glucose [24][25][26][27][28][29][30][31] or lipid metabolism [31][32][33][34][35][36][37][38][39], there exists a relative paucity of studies exploring the impact of expression of genes regulating amino acid uptake in breast cancer. Therefore, we elected to focus the current study on the expression of LAT1, which transports large amino acids including leucine, isoleucine, valine, phenylalanine, methionine, tyrosine, histidine, and tryptophan into the cell, and its relationships with body weight, tumor cell proliferation, and immune infiltration.…”
Section: Discussionmentioning
confidence: 99%